Problematyka konwergencji gospodarczej krajów i regionów - Markowska, Małgorzata; Sobczak, Elżbieta (The economic convergence problems of countries and regions, 2008)
The objective of the hereby article is to analyze diversification changes of the level of development referring to countries and regions in the unified Europe in the perspective of economic convergence theory. There was taken up an attempt of assessing whether and to what extend the convergence occurs with reference to 25 European Union countries as well as its 254 regions of NUTS-2 level. There was also performed an analysis of interdependence between the GDP per capita level and its dynamics. The study covers the years 1995-2003.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 127-138